Genetic improvement of beef bull semen attributes - Butler, Madison Leigh (Kansas State University, 2020)
The genetic basis of fertility of beef bulls collected for artificial insemination (AI) is unclear due to the lack of research and published literature. Researching beef bull fertility traits has the potential to increase the rate of genetic gain, decrease the generation interval, and ultimately allow more genetic improvement in the beef herd not only in the United States, but around the world. In order to drive this genetic gain, quantifying the genetic parameters of beef bull fertility traits is necessary. The objectives of this thesis were to estimate the genetic parameters of beef bull fertility traits and perform a genome-wide association study (GWAS) to identify regions of the genome associated with fertility. Beef bull fertility phenotypes including semen volume (VOL), concentration (CONC), number of spermatozoa (NSP), initial motility (IMOT), post-thaw motility (PTMot), three-hour post-thaw motility (3HrPTMot), percentage of normal spermatozoa (%NORM), primary abnormalities (PRIM), and secondary abnormalities (SEC) on 1,819 Angus bulls were obtained from two bull semen collection facilities. Pedigree and genomic information was provided by the American Angus Association. Variance components were estimated using single-step genomic best linear unbiased prediction (ssGBLUP). All fertility traits were lowly heritable with high repeatabilities. Genetic correlations among the traits varied from low to high. Results from the GWAS indicated there are several regions of the genome associated with previously-reported fertility quantitative trait loci (QTL). While the heritabilities for these traits were low, findings in the current research indicate these traits could be improved by utilizing genetic selection tools for beef bull fertility. Rapidly changing genetic selection tools paired with the ability to obtain thousands of beef bull fertility phenotypes from bull semen collection facilities provide an opportunity to improve beef bull fertility.
Keywords: Artificial insemination; Fertility; Heritability; Correlation; Genome-wide association study; QTL